Loop quantum gravity for the bewildered the self-dual approach revisited - Bilson-Thompson, Sundance (Springer, 2024)
This second edition offers a comprehensive introduction to loop quantum gravity (LQG) in self-dual variables, including the necessary prerequisites. Additionally, it delves into various significant research areas that have emerged in recent years. New content (including an entirely new chapter dedicated to dynamics of quantum spacetime) explores the description of spin networks and spin-foams, their historical development as well as connections to tensor networks, BF theory, and emerging approaches including the spinorial representation of LQG, SU(2) coherent states, and group field theory. Furthermore, the book provides expanded appendices covering essential tools and concepts, such as the connection between information theory and entropy, and overviews of group theory and differential geometry. All topics are presented from a non-expert perspective, ensuring self-containment and accessibility. The primary aim of this second edition remains helping researchers, bewildered bythe vast array of topics within this rapidly growing field of quantum gravity, to gain a fundamental understanding of the current developments